Improving the Quality of Public Services Through Effective Planning - Yanti, Fitri Darma; Tivani, Tivani; Filosofia, Ziada; Erinaldi, Erinaldi (CV. Civiliza Publishing, 2025)
Public services are one of the main tasks of the government in meeting the needs and interests of the community. However, the quality of public services in a number of government agencies is still considered not optimal. One of the main causes is planning that has not been carried out effectively and thoroughly. This paper aims to describe the important role of effective planning in improving the quality of public services, as well as examine how structured planning can be the basis for the creation of good governance. This research uses a literature review approach, which is a research method that is carried out by collecting various written sources such as scientific journals, books, and other documents that discuss the implementation of Public Service Quality through Effective Planning. This method aims to describe and analyze the quality of public services through the concept of planning, service quality indicators, and practical experience in public services.